Implications of The Philosophy of Materialism on Education in Indonesia - Yusuf, Arba’iyah; Rohmaniyah, Vivid (Indonesian Journal of Teaching and Learning, 2025)
The philosophy of materialism is a school of thought that emphasizes that the main reality in life is material. The implications of this philosophy for education in Indonesia include various aspects, ranging from the curriculum, teaching methods, to the purpose of education itself. In an education system influenced by materialism, the orientation of learning focuses more on pragmatic aspects and material outcomes, such as technical skills and economic achievement, compared to the development of moral and spiritual values. As a result, there is a paradigm shift in education that focuses more on utilitarian aspects and the reduction of human values. This article will analyse the impact of materialism philosophy on education in Indonesia and offer a critical perspective to find a balance between material and spiritual aspects in the education process.